Efektivitas Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Untuk Meningkatkan Hasil Belajar Bahasa Arab Siswa Madrasah Ibtidaiyyah - Fathi Hidayah; Riza Faishol (Universitas Yudharta Pasuruan, 2019)
The method of learning Arabic continues to change from time to time. Teachers as producers of learning methods must always choose the right learning methods for their students. Arabic is not a sacred language used as a means to convey God's language, but Arabic can also be delivered in a pleasant packaging. The Islamic Elementary School as a basic level in learning Arabic must help create the impression that Arabic is a language that is fun and important to learn. The 2013 curriculum in Arabic subjects has facilitated teachers to design innovative and student-centered learning. This makes it easier for teachers to choose the latest learning models to deliver the material, one example is cooperative learning. This study aims to determine the effectiveness of the application of the Think Pair Share type of cooperative learning in Arabic subjects in The Islamic Elementary School. This learning model is used with the aim of improving student learning outcomes that have not yet reached the minimum completeness value.